Efficacy of injectable platelet-rich fibrin in the erosive oral lichen planus: a split-mouth, randomized, controlled clinical trial - ÜNVER, TUĞBA; Saglam, Ebru; TOPRAK, ALİ; Ozsagir, Zeliha Betul; Unver, Tugba; Alinca, Suzan Bayer; Toprak, Ali; Tunali, Mustafa (My University, 2021)
Objective: Our study compared the effects of injectable platelet-rich fibrin (i-PRF) with those of corticosteroids in the treatment of erosive oral lichen planus (EOLP). Methodology: This split-mouth study included 24 individuals diagnosed histopathologically with bilateral EOLP. One bilateral lesion was injected with i-PRF, whereas the other was injected with methylprednisolone acetate in four sessions at 15-day intervals. Visual analog scale (VAS) for pain and satisfaction, oral health impact profile scale-14, and the lesion size were used. Results: The intragroup comparisons showed a significant decrease in VAS-pain and lesion size in both the i-PRF group (from 81.88 +/- 17.74 to 13.33 +/- 18.34, and from 4.79 +/- 0.41 to 1.88 +/- 1.08, respectively) and the corticosteroid group (from 80.21 +/- 17.35 to 23.33 +/- 26.81, and from 4.71 +/- 0.46 to 2.21 +/- 1.35, respectively) in the 6th month compared to baseline (p<0.001). Moreover, VAS-satisfaction increased significantly in both the i-PRF group (from 26.67 +/- 17.8 to 85.63 +/- 16.24) and the corticosteroid group (from 28.33 +/- 17.05 to 74.38 +/- 24.11) in the 6th month compared to baseline (p<0.001). However, no significant difference in any value occurred in the intergroup comparisons. Conclusion: In patients with EOLP, both methods decreased pain and lesion size similarly, and both increased satisfaction. Therefore, the use of i-PRF may be considered an option in cases refractory to topical corticosteroid therapy. Biochemical and histopathological studies are required to reveal the mechanism of i-PRF action in EOLP treatment.
Keywords: Corticosteroid; Oral lichen planus; Platelet-rich fibrin; Patient reported outcome measures; Wound healing